2005
DOI: 10.1109/tits.2005.853705
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Microscopic Car-Following Behavior

Abstract: Abstract-Microscopic traffic-simulation tools are increasingly being applied to evaluate the impacts of a wide variety of intelligent transport systems (ITS) applications and other dynamic problems that are difficult to solve using traditional analytical models. The accuracy of a traffic-simulation system depends highly on the quality of the traffic-flow model at its core, with the two main critical components being the car-following and lane-changing models. This paper presents findings from a comparative eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(110 citation statements)
references
References 17 publications
1
108
0
1
Order By: Relevance
“…10 A description of the differences between those models is out of scope of this paper. We refer the interested reader to [36]. We only list here the widely used models in traffi c simulations.…”
Section: Car Following Modelsmentioning
confidence: 99%
“…10 A description of the differences between those models is out of scope of this paper. We refer the interested reader to [36]. We only list here the widely used models in traffi c simulations.…”
Section: Car Following Modelsmentioning
confidence: 99%
“…Car following models: Describe the behavior of each driver in relation to its neighboring vehicles (Panwai and Dia, 2005).…”
Section: Basic Equation Of Traffic Stream Modelmentioning
confidence: 99%
“…The EM showed that the two reactive agent-based models (Fuzzy ARTMAP and Back Propagation networks), performed better than the Gippsbased models. [12].…”
Section: A Simulation Resultsmentioning
confidence: 99%
“…It should be pointed out that Panwai and Dia [12] also used the same time series data set to test the performance of car following models in three well-known traffic simulators: AIMSUN, VISSIM, and PARAMICS. The results are shown in Table 5 below.…”
Section: A Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation